A family of multi-color anthracene carboxyimides: Synthesis, spectroscopic properties, solvatochromic fluorescence and bio-imaging application. (April 2017) - Xu, Junchao; Niu, Guangle; Wei, Xiaofang; Lan, Minhuan; Zeng, Lintao; Kinsella, Joseph M.; Sheng, Ruilong
Abstract: A family of anthracene carboxyimides with multi-color fluorescence have been successfully prepared, and their spectroscopic properties were investigated by UV–vis absorption spectroscopy, steady-state and time-resolved fluorescence spectroscopy. The photostability and solvatochromic fluorescence in organic solvents were also investigated. The parent anthracene carboxyimide4a displays very strong green fluorescence (ΦF = 0.91 in EtOH), good pH stability and photostability, as well as a large Stokes shift. By attachment of different substituents at the 10-position of the anthracene carboxyimide, the fluorescence maxima could be effectively modulated from 500 nm to 615 nm. The 10-(picolylamine) substituted anthracene carboxyimides5a and5b exhibit large Stokes shifts (>80 nm) and significant positive solvatochromic fluorescence in organic solvents due to their intramolecular charge-transfer (ICT) character. Furthermore, cell staining experiments indicate that anthracene carboxyimides have excellent cell membrane permeability and good photo-bleaching resistance in living cells. Particularly, compound5a is a specific mitochondria-targeting dye with red fluorescence. All these features enable anthracene carboxyimides to serve as promising candidates for bio-labeling/imaging applications. Graphical abstract: Highlights: A family of anthracene carboxyimides with multi-color fluorescence have been successfully prepared. The steady-state, time-resolved and solvatechromic fluorescence of the anthracence carboxyimides could be modulated by changing the substitution groups. The anthracene carboxyimides shows high photostability and good cell staining properties. Red fluorescent5a shows a specific mitochondria-targeting effect.